Dampak Korupsi terhadap perekonomian di Indonesia - Rizky Subhan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Corruption remains a significant barrier to sustainable economic development in Indonesia, leading to inefficiencies in resource management and diminishing public trust in state institutions. This study aims to analyse the impact of corruption on economic growth, investment, and societal welfare through a qualitative approach using literature review. The findings indicate that corruption has a significant negative relationship with economic growth, hindering foreign investment inflows and exacerbating economic inequality. High levels of corruption create an environment of uncertainty, deterring potential investors who seek stable and transparent markets. Data reveal that Indonesia's low Corruption Perception Index (CPI), which scored 34 out of 100 in 2023, contributes to stagnant investment and poor public service quality. Moreover, corruption diverts public funds away from essential services such as education and healthcare, further entrenching poverty and inequality. To mitigate the effects of corruption, comprehensive strategies are needed, including enhancing transparency in government spending, strengthening oversight institutions like the Corruption Eradication Commission (KPK), and fostering active community participation in governance. Public awareness campaigns and education on the detrimental effects of corruption can empower citizens to demand accountability from their leaders. Additionally, implementing digital solutions for public procurement and financial management can reduce opportunities for corrupt practices. Through collaboration among various stakeholders, including government, civil society, and the private sector, it is hoped that anti-corruption efforts can promote better economic growth and equitable welfare distribution in Indonesia. Ultimately, addressing corruption is not only crucial for improving economic performance but also for ensuring social justice and enhancing the overall quality of life for all citizens.